2015
DOI: 10.1111/jsm.12969
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Concerns after (Pelvic) Radiotherapy: Is There Any Role for the Radiation Oncologist?

Abstract: Radiation oncologists generally perform sexual counseling in case of pelvic radiation therapy, but not consistently in case of gastrointestinal, breast, and other cancers. The majority of radiation oncologists considered counseling on sexual functioning as a part of their job, some also pointed at the referring specialist or general practitioner. The findings suggest that awareness about sexual dysfunction is present among radiation oncologists, but responsibility for active counseling is uncertain. Results em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…and a nephrologist (H.B.). The structure and design of the questionnaire were derived from questionnaires used in previous studies regarding sexuality and health‐care providers [20–24], with items based on issues identified by the authors and in literature. The survey was pilot tested by nephrologists and residents from the Leiden University Medical Centre Department of Nephrology (n = 7).…”
Section: Methodsmentioning
confidence: 99%
“…and a nephrologist (H.B.). The structure and design of the questionnaire were derived from questionnaires used in previous studies regarding sexuality and health‐care providers [20–24], with items based on issues identified by the authors and in literature. The survey was pilot tested by nephrologists and residents from the Leiden University Medical Centre Department of Nephrology (n = 7).…”
Section: Methodsmentioning
confidence: 99%
“…Personal discomfort was also cited as a factor even when taking into account professional factors. Some healthcare professionals felt that discomfort and lack of confidence could be a barrier, even with sufficient knowledge and understanding of the issue [36,49,40,50,51]. Sex was also often referred to as 'risky' or 'taboo' subject [33,38] with meaningful discussion often limited even when healthcare professionals were normally able to talk about other 'sensitive' issues [32,44].…”
Section: Theme 1: Individual and Societal Attitudes To Sex And Sexualmentioning
confidence: 99%
“…Moreover, they face several other barriers, such as uncomfortable feelings, insufficient knowledge, lack of training, lack of time and over involvement in aspects of patients' personal lives. Oncology care providers do, however, consider sexual function to be an important topic [18][19][20][21]. During cancer treatment, patients are treated by different professionals within a multidisciplinary team.…”
Section: Introductionmentioning
confidence: 99%
“…It is not always clear which member of the team is responsible for addressing sexual function. Studies among different Dutch oncology care providers revealed that members of the oncology team, like radiation oncologists, oncology nurses and oncology surgeons, see some role for themselves in sexual function counselling, but all point to the medical oncologist to bring up the subject [19][20][21].…”
Section: Introductionmentioning
confidence: 99%